Incidencia de la inclusión financiera sobre la rentabilidad en la Caja Municipal de Ahorro y Crédito Trujillo 2010-2021 - Varas Guzmán, César Antony (2022)
This research paper analyzes the relationship of financial inclusion with indicators of the total amount of loans placed, administration expenses, number of correspondent ATMs and number of ATMs on profitability through the indicator of net profits in the CMAC Trujillo de 2010 to 2021 with monthly data. Considering a non-experimental design of longitudinal scope of a descriptive and correlational type, the evolution of financial inclusion and profitability is analyzed, with the econometric estimation under the method of least squares, we find that the incidence ratio is that each increase in 1% of the loans placed increases profitability by 0.021%, while a 1% increase in administrative expenses, which include the maintenance of ATM operations, increases profitability by 0.012%.